ANALISA PENDAPATAN USAHATANI DAN UPAYA PENINGKATAN PRODUKTIVITAS GAMBIR (Uncaria gambir Roxb) DI KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA - Dina Arfianti Saragih (Bernas : Jurnal Penelitian Pertanian, 2016)
This research analyzes benefit and profit of Gambier farming and identifies the factors for its productivity. I surveyed 30 farmers in Kecamatan Harau, Lima Puluh Kota district, where Gambier is widely cultivated. Farming analysis is applied for benefit and profit calculation. Cobb Douglass model is utilized for factors of productivity identification. Farmers cultivate varies hectares of land for Gambier, from 1-3 Ha. Its productivity is considerably low, 737.5 Kg/Ha/years. The benefit is Rp. 16.093.475,-/ year, and the profit is Rp 288.208,20,-/Ha/yearin average respectively. Farmers’ monthly income from Gambier farming is Rp.1.341.122,917 and monthly profit is Rp. 690.684,02,- in average. In addition, fertilizer (urea), herbicide (round up), plant age, labor, and farmer’s education are the factors which significantly correlated (F test) to Gambier’s productivity. However, it is not significantly partial correlation (t test) betweenthose factors to Gambier productivity. Based on these findings, farmers have to manage their Gambier farming properly by using its residue for organic fertilizer and apply good soil management.